THU0403 Scd163 in Adult Onset Still's Disease: A Biomarker for Macrophage Activation Related to Hyperferritinemia. (10th June 2014) - Colafrancesco, S.; Priori, R.; Astorri, E.; Perricone, C.; Agmon-Levin, N.; Blank, M.; Shoenfeld, Y.; Valesini, G.
Abstract : Background: Adult onset Still's disease (AOSD) has been recently included in a new group of diseases namely "The hyperferritinemic syndromes" where ferritin heavy (H) and light (L), possibly macrophage derived, seems to have a pathogenic role. CD163 is a "scavenger receptor", mainly expressed on active macrophages and released by shedding in the sera (sCD163). The over-expression of this molecule in several inflammatory conditions, including sepsis, has been described. Objectives: To determine the levels of sCD163 in AOSD patients in order to evaluate its utility as biomarker of disease and its correlation with ferritin. Further, to evaluate the expression and histologic localization of CD163 and ferritin in a lymph node from a patient with AOSD. Methods: We measured sCD163 (ELISA; IQ Products ) and ferritin serum levels (LIASON, Diasorin), in patients with AOSD (Yamaguchi criteria) and control groups [sepsis (ACCP/SCCM Consensus Conference criteria), healthy subjects (NHS)]. AOSD patients scoring≥4 criteria (Rau's criteria) were defined active. Immunohistology was performed on paraffin embedded lymph node from a patient with AOSD in order to detect CD163 (CD163 Mouse mAb, Fisher Scientific) and ferritin (Anti-Ferritin Light and Heavy chain antibodies, ABCAM) . A tonsil from a healthy subject was used as control. Results: Thirty four patients with AOSD (21 active–13 non active) (F 22, M 12, mean age 38.1 years, range 17-64), 18 patients with sepsis and 22 NHS were enrolled. Mean serum levels of sCD163 and ferritin are reported in table. In NHS mean sCD163 was 2.56 mg/l (SD ±1.16). In active AOSD mean sCD163 level was significantly higher than "non active" (p=0.02). AOSD and sepsis had mean sCD163 significantly higher than NHS (p<0.001). No difference in sCD163 levels between AOSD and sepsis was detected. sCD163 was positively correlated to ferritin (Spearman's test) (p=0.0045; r=0.4755) only in AOSD. In active AOSD mean ferritin serum level was significantly higher than in sepsis (p<0.007). By immunohistochemical analysis CD163 was detected equally distributed into the B and T area of both lymph node and tonsil. Both ferritin subunits were highly expressed only in the B cell area of the lymph node while it was possible to find them widely expressed also in the T and B cell areas of the tonsil control tissue. Conclusions: This is the first study on the evaluation of sCD163 in patients with AOSD. Since this molecule was significantly increased in patients with active AOSD, sCD163 may represent a possible marker of disease activity. sCD163 positively correlated with ferritin only in AOSD patients suggesting that in this condition hyperferritinemia is related to macrophage activation. Further, while this marker is diffusely expressed in the AOSD lymph node, for the first time we demonstrate that ferritin is expressed only in the B cell area supporting a role of this molecule as antigen in course of AOSD. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4229